Low resistance n-contact for UVC LEDs by a two-step plasma etching process. (4th August 2020) - Cho, H K; Kang, J H; Sulmoni, L; Kunkel, K; Rass, J; Susilo, N; Wernicke, T; Einfeldt, S; Kneissl, M
Abstract: The impact of plasma etching on the formation of low-resistance n-contacts on the AlGaN:Si current spreading layer during the chip fabrication of ultraviolet light-emitting diodes (UV LEDs) emitting at 265 nm is investigated. A two-step plasma etching process with a first rapid etching using BCl3 /Cl2 gas mixture and a second slow etching step using pure Cl2 gas has been developed. The etching sequence provides smooth mesa side-walls and an n-AlGaN surface with reduced surface damage. Ohmic n-contacts with a contact resistivity of 3.5 × 10 −4 Ωcm 2 are obtained on Si-doped Al0.65 Ga0.35 N layers and the operating voltages of the UVC LEDs were reduced by 2 V for a current of 20 mA.